On the diagnostic characters of the genus Gibbesia (Crustacea: Stomatopoda: Squillidae) - Bento, Rodrigo Tadeu; Dall´occo, Paola Lupianhes; de Melo, Gustavo Augusto Schmidt (Zootaxa, 2008)
Manning & Heard (1997) proposed the creation of the genus Gibbesia for Squilla neglecta Gibbes, 1850, based on the presence of five teeth on the dactylus of the raptorial claw and on the absence of the mandibular palp, the latter character not being found in any other species belonging to the genus Squilla.